STRATEGI STRATEGI PEER LESSONS SOLUSI TERHADAP MASALAH KEMAMPUAN BERPIKIR KRITIS DAN KETERAMPILAN KOMUNIKASI KELAS V MADRASAH IBTIDAIYAH MUHAMMADIYAH - ARMIA (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2020)
This research is motivated by students' critical thinking skills and communication skills that have not been maximally developed in the learning process. During this time, the implementation of learning is dominated by the use of lecture methods whose activities are more centered on the teacher. This research uses a quantitative approach, a quasi-experimental method with the Nonequivalent Control Group design. The population in this study were all sample students in class V with 41 students. Data collection tools used were test questions, observation sheets, questionnaires, and documentation. Based on the analysis of the data obtained the following research questionnaire: (1) students are still experiencing difficulties in answering questions that require the analysis process. (2) students are still unable to identify problems related to the surrounding environment (3) students have not been able to have active discussions in the learning process, so that it can be concluded that to answer the problems above it is necessary to have a strategy that is an active learning strategy type of peer lesson can be applied as one strategies in learning Natural Science in the Water Cycle Material because based on the documentation of student learning outcomes the material is very difficult for students to understand